Republic of Kazakhstan : Report on the Observance of Standards and Codes (ROSC)-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2003)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for the Republic of Kazakhstan. The fiscal reporting and dissemination of information in Kazakhstan has already achieved a sound level of practice, and can be built upon with relatively little further effort. Promising work has also begun in establishing a disciplined medium-term budget framework. Such a framework will be essential to enable policy proposals to be appraised in light of their long-term costs, which is of central importance in linking development programs to recurrent costs and in examining social security trends.